Comparison and Correlation Between Attitude and Process Skills in Mathematics: The Case of Public and Islamic Middle School in Indonesia - Kamid, Kamid; Syaiful, Syaiful; Ramalisa, Yelli; Sufri, Sufri; Triani, Elza (Jurnal Pendidikan Progresif, 2022)
Comparison and Correlation between Attitude and Process Skills in Mathematics: The Case of Public and Islamic Middle School in Indonesia. Objectives: to find out the comparison and relationship between process skills and students' interest in learning mathematics in junior high school. Methods: using a quantitative descriptive survey design. A total of 140 students from SMPN 35 Batanghari and MTsN 5 Batanghari were purposively selected as research samples. Data analysis used descriptive and inferential statistics. Findings: The results of the t-test of students' process skills and interest in learning at SMPN 35 Batanghari and MTsN 5 Batanghari obtained sig. (2-tailed) is less than 0.05. Analysis of the correlation between the interests and process skills of students obtained the value of sig. (2-tailed) in each school is less than 0.05. Conclusion: There are differences in students' interest and process skills between each school and students' interest is significantly correlated with process skills. Interest in learning will create curiosity, so that it can improve students' process skills. Keywords: mathematics, process skills, interest.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202210